Answer:
yuh
Step-by-step explanation:
add me on rbIx and follow me IMAO : ivxvxi
Answer:
-6x^2-288
Step-by-step explanation:
18x - 432 - 18x - 6x² +144
Combine like terms
-6x^2+18x-18x-432+144
-6x^2-288
Answer:
74
Step-by-step explanation:
fg(x)=f[g(x)]
=f(-4x+7)
=3(-4x+7)+5
=-12x+26
When x=-4,
fg(-4)=-12(-4)+26
=74
Answer: 5x^2 + 3x + 1
Step-by-step explanation:
1.) Put the two equations together into an addition problem.
<em>3x^2 + 4x + 2x^2 - x + 1</em>
2.) Combine like terms.
<em>3x^2 + 2x^2 = 5x^2</em>
<em>4x - x = 3x</em>
<em>1 = 1</em>
3.) Order the like terms together.
<em>5x^2 + 3x + 1</em>